Management of a Giant Ovarian Mucinous Cyst in Late Pregnancy: A Combined Surgical Approach - Arya Ady Nugroho; Yuditiya Purwosunu (PT Dexa Medica, 2026)
Background: Adnexal masses complicating pregnancy are relatively rare, with an incidence of 1–5% of all pregnancies. Most are benign and may regress spontaneously; however, large or persistent cysts require careful management because of risks such as torsion, rupture, obstruction of labor, and malignancy. Ovarian mucinous cystadenomas are particularlyuncommon but may grow to giant sizes, causing maternal discomfort and fetal complications, including malpresentation. The optimal timing and mode of surgery depend on gestational age and tumor characteristics. In late pregnancy, concurrent cesarean section and adnexal surgery is considered safe and effective, minimizing the need for repeated laparotomy. Case presentation: We report a 30-year-old gravida 3, para 1, abortus 1 woman at 38 weeks of gestation with a giant right ovarian cyst suspected to be mucinous cystadenoma. The patient presented with a transverse fetal lie without acute complications. Ultrasonography demonstrated a multilocular homogeneous cyst extending to the xiphoidprocess without solid components, classified as O-RADS 3, with a risk of malignancy index (RMI) 39. Tumor markers levels were within benign ranges. At term, the patient underwent spinal anesthesia and Pfannenstiel laparotomy during cesarean section. A healthy male infant weighing 2,720 g was delivered, with Apgar scores of 8 and 9 at 1 and 5 minutes respectively. Right salpingo-oophorectomy was also performed. The estimated blood loss was 600 ml, urine output was 300 ml, with uneventful postoperative recovery. The contralateral adnexa were normal. Conclusions: This case highlightsthe challenges of managing a giant ovarian mucinous cyst during pregnancy. Concurrent cesarean section and salpingooophorectomyat term provided an optimal approach, to ensure maternal and neonatal safety while preventing recurrence risk. Multidisciplinary planning and individualized surgical decisions making remain essential for achieving favorable outcomes in such complex cases.